The Influence of Investors' Perceptions of Stock Influencer Credibility on Herding Behavior With Financial Literacy as a Moderating Variable - Anshori, Syaiful; Makaryanawati; Restuningdiah, Nurika (International Journal of Business and Applied Economics, 2024)
This study aimed to analyze the effect of investor perceptions on stock influencers' credibility on herding behavior with financial literacy as a moderating variable. This research was conducted in the city of Malang. The number of samples in this study was 100 respondents. The Lemeshow formula determined it. Data collection was carried out through a questionnaire. The data analysis technique used in this study is Moderated Regression Analysis (MRA). Based on the analysis results, the credibility of stock influencers positively affects herding behavior. Financial literacy can weaken the influence of stock influencer credibility on herding behavior.